Kodiranje enciklopedij - Kovač, Miha (Teorija in praksa, 1999)
The author examines the historic formation of the Slovene national encyclopedia, showing that the articles in Encylopedia were ideologically limited to Marxist ideology. However, the cultural determination of the whole project was even more important. Namely, the Encyclopedia included only articles and notions concerning Slovenian cultural heritage, and was therefore conceptually strictly autarchic project.
Keywords: enciklopedije; leksikoni; vrednotenje; Enciklopedija Slovenije; Encyclopedia of Slovenia; nacionalne enciklopedije